2008
DOI: 10.1016/j.exer.2007.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary melatonin on photoreceptor survival in the rat retina: An ocular toxicity study

Abstract: Previous studies have shown that melatonin treatment increases the susceptibility of retinal photoreceptors to light-induced cell death. The purpose of this study was to evaluate under various conditions the potential toxicity of dietary melatonin on retinal photoreceptors. Male and female Fischer 344 (non-pigmented) and Long-Evans (pigmented) rats were treated with daily single doses of melatonin by gavage for a period of 14 days early in the light period or early in the dark period. In another group, rats we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…One promising candidate is melatonin (MEL), a naturally occurring hormone that is also available as an over-the-counter dietary supplement. MEL possesses many of the fundamental characteristics of a central nervous system (CNS) therapeutic including low toxicity [ 10 , 11 , 12 ], an ability to cross the blood-brain-barrier [ 13 , 14 , 15 ], and receptors that bind MEL in the CNS [ 16 , 17 , 18 , 19 ]. While the therapeutic effects of MEL in human TBI remain understudied, MEL has demonstrated beneficial effects in pre-clinical models of several CNS disorders, including conditions with similar pathology and symptoms profiles, to TBI such as: Huntington’s disease [ 20 ], Alzheimer’s disease [ 21 ], amyotrophic lateral sclerosis [ 22 , 23 ], stroke [ 24 , 25 ], sepsis-induced brain dysfunction [ 21 ], and spinal cord injury [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…One promising candidate is melatonin (MEL), a naturally occurring hormone that is also available as an over-the-counter dietary supplement. MEL possesses many of the fundamental characteristics of a central nervous system (CNS) therapeutic including low toxicity [ 10 , 11 , 12 ], an ability to cross the blood-brain-barrier [ 13 , 14 , 15 ], and receptors that bind MEL in the CNS [ 16 , 17 , 18 , 19 ]. While the therapeutic effects of MEL in human TBI remain understudied, MEL has demonstrated beneficial effects in pre-clinical models of several CNS disorders, including conditions with similar pathology and symptoms profiles, to TBI such as: Huntington’s disease [ 20 ], Alzheimer’s disease [ 21 ], amyotrophic lateral sclerosis [ 22 , 23 ], stroke [ 24 , 25 ], sepsis-induced brain dysfunction [ 21 ], and spinal cord injury [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…MEL is produced throughout the body, with the primary site of production being the pineal gland. MEL is available as a medication and over-the-counter supplement and has a known low toxicity profile in both human and animal studies with few reported adverse effects even at very high doses [10]. Existing evidence shows endogenous MEL levels are altered in TBI-survivors in a time-point and biosample-dependent manner [11,12]; thus, MEL may be important in the body’s response to TBI and there may be an opportunity to improve outcomes via therapeutic administration of MEL.…”
Section: Introductionmentioning
confidence: 99%
“…A later study in the P23H rat model of RP has revealed that exogenous melatonin prevents vision loss and circadian rhythmicity alteration [111]. However, and as already mentioned, Wiechmann and colleagues [105] have observed a greater loss of photoreceptor cells after melatonin intake plus exposure to bright light. This opposite effect may be explained by the different animal model used.…”
Section: Retinitis Pigmentosamentioning
confidence: 93%
“…However, Wiechmann and colleagues [105] have observed a harmful effect of dietary melatonin on rat photoreceptor cell survival in response to bright light. Hence, it has been suggested that the time for melatonin intake during the day should be considered before the organization of a clinical trial [102].…”
Section: Age-related Macular Degenerationmentioning
confidence: 97%